Fatal sequelae of hydrogen sulphide poisoning. Issue 5 (20th April 2023) - Goolam, Nadirah; Bhikoo, Raisa; Koegelenberg, Coenraad F. N.; Lalla, Usha
Abstract: Hydrogen sulphide (H2 S) is a toxic, colourless gas abundantly present at waste plants and sewers due to the presence of anaerobic forming organisms. Hazardous exposure via accidental, intentional or occupational contact results in endothelium disruption, cellular instability, decreased respiratory functional capacity and cardiovascular compromise with a rapidly fatal clinical course. Clinical manifestations are variable depending on the level of exposure with moderate or heavy exposure associated with rapid fatality. Respiratory manifestations remain the primary reason for admission to critical care facilities. We describe a case of a 30‐year‐old sewer worker with a history of heavy accidental occupational exposure of inhaled H2 S admitted with acute respiratory distress syndrome and a rapid respiratory decline ultimately leading to death. Abstract : We describe a case of a 30‐year‐old sewer worker with a history of heavy accidental occupational exposure of inhaled H2S admitted with acute respiratory distress syndrome and a rapid respiratory decline ultimately leading to death.